Barriers and facilitators to data-based decision making in Australian early childhood education and care: A qualitative study - Shauna Sherker; Karen Villanueva; Ruth Beatson; Caitlin M. Macmillan; Wan Yi Lee; Olivia Hilton; Carly Molloy; Sharon Goldfeld (Social Sciences and Humanities Open)
Early childhood education and care (ECEC) provides a critical platform for children's development in the early years. To be of benefit to all children, ECEC must deliver on three key areas: availability (quantity), quality and participation (reach and dose). Lead indicators can be derived and applied to help service providers drive equitable systems change. Yet there is little evidence that the ECEC sector is able to utilise lead indicators and data for this purpose. In this study, we used the Theoretical Domains Framework (TDF) and the Capability, Opportunity, and Motivation model of Behaviour (COM-B) to explore barriers and facilitators to data-utilisation behaviours (collecting, reporting, and using lead indicator data) by ECEC service providers. Semi-structured interviews with ECEC service staff and managers were conducted between May and November 2022. Barriers spanned issues of capability (knowledge), opportunity (data systems and processes, data quality, data availability, resources) and motivation (data culture, trust, pressure). Important facilitators related to capability (ability to use data systems, cognitive skills and interpersonal skills), opportunity (environmental context and resources or social influences) and motivation (reinforcement and professional/social role and identity). Multipronged strategies, including introducing practical data systems, ensuring adequate staff resources, providing additional funding and data-use training, and developing organisational data culture that promotes trust could increase lead indicator data use in ECEC. These findings can guide service improvement efforts and help to ensure that children and families can access high-quality services when and where they need them.